Building the economic resilience of small states - Briguglio, Lino (Formatek Publishing MT, 2006)
Attempts to explain what needs to be done to enable inherently vulnerable small states build up their economic resilience in order to withstand economic shocks. Emhasises policies that promote macroeconomic stability and microeconomic policies that enhance flexibility in market adjustment.